2021
DOI: 10.3390/ijerph18126487
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Platform Comparative Study of Public Concern on Social Media during the COVID-19 Pandemic: An Empirical Study Based on Twitter and Weibo

Abstract: The COVID-19 pandemic has created a global health crisis that has affected economies and societies worldwide. During these times of uncertainty and crisis, people have turned to social media platforms as communication tools and primary information sources. Online discourse is conducted under the influence of many different factors, such as background, culture, politics, etc. However, parallel comparative research studies conducted in different countries to identify similarities and differences in online discou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 69 publications
(88 reference statements)
0
12
0
Order By: Relevance
“…If you don’t get vaccinated, your immune system may not be damaged and you may not have ADE reactions”. Previous studies have determined that anti-vaccine messages often revolve around potential side effects, adverse reactions to vaccines, misinformation and conspiracy theories [ 36 ]. Our results also confirm that anti-vaccine messages remain in the face of the SARS-COV-2 variant.…”
Section: Discussionmentioning
confidence: 99%
“…If you don’t get vaccinated, your immune system may not be damaged and you may not have ADE reactions”. Previous studies have determined that anti-vaccine messages often revolve around potential side effects, adverse reactions to vaccines, misinformation and conspiracy theories [ 36 ]. Our results also confirm that anti-vaccine messages remain in the face of the SARS-COV-2 variant.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to a large number of anti-vaccination discussions on Twitter, similar discourse is rare on Sina Weibo [ 47 ]. Previous studies maintained that pro-vaccine information usually revolves around potential side effects, adverse vaccine reactions, misinformation, and conspiracy theories [ 35 ]. Apart from conspiracy theories, anti-vaccination discussions among the Chinese public showed similar topics.…”
Section: Discussionmentioning
confidence: 99%
“…They found complex emotions in which anger and fear coexisted with trust, solidarity, and hope. Another study comparing American and Chinese posts on Twitter and Sina Weibo revealed differences in public perceptions of COVID-19 among people in different cultures [ 35 ].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Naïve Bayes model is applied to analyze the collected tweets of the Twitter users to predict their sentiment. Deng et al [11] used data mining approaches and a set of predefined search terms related to COVID-19 to analyze Twitter data. Also, used Latent Dirichlet Allocation (LDA), as topic modeling approach to detect the most popular topics published by the different users to detect and identify the trending topics.…”
Section: Related Workmentioning
confidence: 99%